2007
DOI: 10.1111/j.1442-200x.2007.02370.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant effect of vitamin A on recurrent lower urinary tract infections

Abstract: Vitamin A supplementation may have an adjuvant effect on the treatment of RUTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Despite its intricate relationship with pathogen control, vitamin A is often overlooked as a defense against clinical UTIs or respiratory diseases, particularly in developed countries [47,52]. Our results illustrate the dysfunctional immune parameters and poor outcomes of VAD and encourage clinicians to consider abnormal vitamin A levels as a cause of poor outcome.…”
Section: A Focus On the Cross Regulatory Signals Of Nuclear Receptorsmentioning
confidence: 67%
See 1 more Smart Citation
“…Despite its intricate relationship with pathogen control, vitamin A is often overlooked as a defense against clinical UTIs or respiratory diseases, particularly in developed countries [47,52]. Our results illustrate the dysfunctional immune parameters and poor outcomes of VAD and encourage clinicians to consider abnormal vitamin A levels as a cause of poor outcome.…”
Section: A Focus On the Cross Regulatory Signals Of Nuclear Receptorsmentioning
confidence: 67%
“…Acute pyelonephritis is a frequent cause of serious bacterial UTIs in infants, with renal scarring followed by hypertension and chronic renal failure being the most common long-term sequelae [40][41][42][43][44]. Vitamin A/retinoid supplementation can be protective in some (but not all) cases [39,[45][46][47][48][49][50][51][52], perhaps in part by preventing the adhesion of bacteria to respiratory epithelium [33].…”
Section: Vad Keratinizing Metaplasia Utis and Respiratory Tract Dismentioning
confidence: 99%
“…A randomised, placebo controlled trial of vitamin A to prevent recurrent UTI in children [43] showed a reduced rate of UTI in the follow-up period, but only 24 children participated so the estimate of efficacy is imprecise and there are also concerns over selection bias.…”
Section: Complementary Treatmentsmentioning
confidence: 99%
“…The results of this study revealed that the vitamin C group had a significantly lower incidence of UTIs than the control group. Similarly, the use of vitamin A in the management of UTIs in children was evaluated by Yilmaz et al (2007). This study tested 24 children, 12 in the vitamin A group who received 200,000 IU of vitamin A, in addition to antimicrobial therapy for 10 days and 12 in the control group who just received the antimicrobial.…”
Section: Dietary Interventionsmentioning
confidence: 99%